Face Shield Making Training for Pkk Women in the Village of Bugul Lor Pasuruan - Afifah, Ani (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2023)
Bugul Lor Village is a village in Panggungrejo District, Pasuruan City, East Java Province. One of the problems faced by residents in Bugul Lor village is that the level of awareness of protecting themselves during a pandemic is still low. Such as implementing physical distancing, using masks, hand sanitizers, and other personal protective equipment. Bugul Lor Village has potential that can be exploited to create a healthy and prosperous society. The community service activities aim to provide training on making face shields in Bugul Lor Village, Panggungrejo District, Pasuruan City, East Java Province. This activity was carried out in August 2020 and was attended by 10 PKK RT/RW mothers: 02/02. The material presented in the training activities is material on making face shields. The implementation team presented the tools and materials needed. The implementation team demonstrated how to make a face shield. Each trainee was asked to try to make a face shield. This activity received a positive response from the training participants. After the activity was carried out, the knowledge and skills of the training participants in making face shields increased.